The facilitator's role in professional learning communities for inclusive education - Matanhire, Vimbayi (My University, 2017)
Professional learning communities (PLCs) for inclusive education are one way of teacher development for inclusive education. Professional learning communities are gradually being adopted in South African schools to equip teachers with knowledge and skills to teach learners from diverse backgrounds. This study investigated the role of the PLC facilitator for inclusive education in a full service school. My study was part of a bigger project that focused on a wide range of professional learning communities’ issues. Data was collected through semi-structured individual interviews of PLC facilitators, observation of PLC sessions and analysis of PLC sessions’ transcripts. Data was analysed using qualitative data analysis where I organised and sorted data into major organising themes and then used an open coding system. Data was presented in the form of figures, tables, excerpts and descriptions. The findings of the study showed that facilitators of PLCs for inclusive education assume multiple roles that contribute to building the community and knowledge for inclusive education among PLC members. Professional learning communities have the potential to dismantle anxieties associated with teaching learners from diverse backgrounds and of diverse abilities. PLCs also have the potential to develop teachers’ knowledge and skills for inclusive education.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Education the Faculty of Humanities, University of the Witwatersrand, 2017
Keywords: Educational leadership--South Africa; Effective teaching--South Africa